Non-linear association between arterial oxygen tension and survival after out-of-hospital cardiac arrest: A multicentre observational study - McKenzie, Nicole; Finn, Judith; Dobb, G.; Bailey, P.; Arendts, G.; Celenza, A.; Fatovich, D.; Jenkins, I.; Ball, Stephen; Bray, Janet; Ho, K.M. (ELSEVIER IRELAND LTD, 2021)
Background: Studies to identify safe oxygenation targets after out-of-hospital cardiac arrest (OHCA) have often assumed a linear relationship between arterial oxygen tension (PaO2) and survival, or have dichotomised PaO2 at a supra-physiological level. We hypothesised that abnormalities in mean PaO2 (both high and low) would be associated with decreased survival after OHCA. Methods: We conducted a retrospective multicentre cohort study of adult OHCA patients who received mechanical ventilation on admission to the intensive care unit (ICU). The potential non-linear relationship between the mean PaO2 within the first 24 -hs of ICU admission and survival to hospital discharge (STHD) was assessed by a four-knot restricted cubic spline function with adjustment for potential confounders. Results: 3764 arterial blood gas results were available for 491 patients in the first 24-hs of ICU admission. The relationship between mean PaO2 over the first 24-hs and STHD was an inverted U-shape, with highest survival for those with a mean PaO2 between 100 and 180 mmHg (reference category) compared to a mean PaO2 of <100 mmHg (adjusted odds ratio [aOR] 0.50 95% confidence interval [CI] 0.30, 0.84), or >180 mmHg (aOR 0.41, 95% CI 0.18, 0.92). Mean PaO2 within 24 -hs was the third most important predictor and explained 9.1% of the variability in STHD. Conclusion: The mean PaO2 within the first 24-hs after admission for OHCA has a non-linear association with the highest STHD seen between 100 and 180 mmHg. Randomised controlled trials are now needed to validate the optimal oxygenation targets in mechanically ventilated OHCA patients.